(untitled) (Altre Modernità, 2016)
The right to information and communication has been traditionally considered one of the pillars of citizenship as well as of the democratic system. However, in the specific case of external citizenship its strategic role is not so evident. In this article, I discuss its implications for the representation and participation of external citizens. Given the general characteristics of Italian residents in Argentina, they represent a privileged case of study. Not only because of the fact that they are the biggest group of Italian residents abroad, but also due to the minority presence of Italian native-speakers among them. This trait turns out to be of great interest in order to know better the role that language barriers play in accessing public information to cast an informed vote. The preliminary results of an ongoing online research on the reception of the Italian broadcaster’s international channel in Argentina indicate that, rather than hinder access, language is, at least for those who are able to understand it, the main reason to tune to it.